2022
DOI: 10.1101/2022.04.06.487425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secreted dengue virus NS1 from infection is predominantly dimeric and in complex with high-density lipoprotein

Abstract: Severe dengue infections are characterized by endothelial dysfunction shown to be associated with the secreted nonstructural protein 1 (sNS1), making it an attractive vaccine antigen and biotherapeutic target. To uncover the biologically relevant structure of sNS1, we extracted the native form of sNS1 from cells infected with either the DENV WT or T164S mutant whose appearance was associated with a dengue outbreak in Cuba. We determined the cryoEM structures of sNS1 and its complex with a monoclonal antibody/F… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 66 publications
2
16
1
Order By: Relevance
“…Compared to the available structures, we present a new subset of antibody-NS1 complex structures at antigen-binding sites between the wing and β-ladder of the NS1 protein. Lastly, we showed that ZIKV isNS1 is found in complex with apoA1; they are dimers docked onto HDL, similar to earlier reports for DENV 30,33 .…”
Section: Introductionsupporting
confidence: 90%
“…Compared to the available structures, we present a new subset of antibody-NS1 complex structures at antigen-binding sites between the wing and β-ladder of the NS1 protein. Lastly, we showed that ZIKV isNS1 is found in complex with apoA1; they are dimers docked onto HDL, similar to earlier reports for DENV 30,33 .…”
Section: Introductionsupporting
confidence: 90%
“…As there were marked differences between ApoA1 and cholesterol subfractions between patients with DF and DHF, and since it was shown that ApoA1 binds to DENV NS1 [24], we wished to evaluate the possible effects of ApoA1 and NS1 together on primary human . CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Effect Of Apoa1 and Ns1 On Primary Human Monocytes In Induci...mentioning
confidence: 99%
“…As there were marked differences between ApoA1 and cholesterol subfractions between patients with DF and DHF, and since it was shown that ApoA1 binds to DENV NS1 [24], we wished to evaluate the possible effects of ApoA1 and NS1 together on primary human monocytes. In order to determine the effect of ApoA1 along with NS1, primary monocytes of 6 individuals were co-cultured with varying concentrations of natural human ApoA1 (specified by the manufacturer as endotoxin free) at various concentrations (195μg/ml, 100μg/ml, 65μg/ml, 10μg/ml, and 1.68μg/ml) together with DENV1 NS1 antigen, that was specified by the manufacturer as endotoxin free (1μg/ml) (Native antigen, UK) for 16 hours.…”
Section: Effect Of Apoa1 and Ns1 On Primary Human Monocytes In Induci...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, ZIKV infection modulates the placenta lipidome for intracellular membrane reorganization (like formation of vesicle pockets on the ER luminal side visualized by TEM imaging) and viral replication . Several reports have also suggested that NS1 affects cholesterol metabolism and triggers proinflammatory responses by interacting with HDL (high density lipoprotein, responsible for reverse cholesterol transport). Recent cryo-EM studies have highlighted the formation of higher order oligomeric states (dimers and hexameric) of NS1 with HDL. , All these studies emphasize the significance of NS1 interaction with lipids and lipoproteins for replication and disease progression inside the host cells. Hence, a molecular level exploration of the interaction of NS1 with cholesterol containing membrane is necessary to understand the formation of NS1-HDL complexes.…”
Section: Introductionmentioning
confidence: 99%